Arctiin abrogates osteoclastogenesis and bone resorption via suppressing RANKL-induced ROS and NFATc1 activation. (September 2020) - Chen, Delong; Ye, Zhen; Wang, Chao; Wang, Qingqing; Wang, Haibin; Kuek, Vincent; Wang, Ziyi; Qiu, Heng; Yuan, Jinbo; Kenny, Jacob; Yang, Fan; He, Jianbo; et al.
Graphical abstract: Note: ARC inhibits osteoclastogenesis by suppressing RANKL-induced MAPK (including JNKs and ERKs), calcium, and NFATc1 signaling pathway, as well as by promoting the expression of ROS scavenging enzymes in Nrf2/Keap1/ARE signaling pathway. Abstract: Osteoporosis, characterized by disrupted bone resorption and formation, is viewed as a global health challenge. Arctiin (ARC) is a main component of Arctium lappa L, which exerts chemopreventive effects against various tumor cells. However, the role of ARC in bone remodeling is still unclear. Here, we first demonstrated that ARC inhibits osteoclast formation and bone resorption function induced by the receptor activator of nuclear factor-κB ligand (RANKL) in a dose- and time-dependent manner without exerting cytotoxic effects. Mechanistic analysis revealed that ARC not only suppresses RANKL-induced mitogen-activated protein kinase (MAPK) and calcium signaling pathways, but also enhances the expression of cytoprotective enzymes that are involved in scavenging reactive oxygen species (ROS). Further, ARC inhibits the activation of the major transcription factor nuclear factor of activated T cells 1 (NFATc1) during RANKL-induced osteoclast formation. Preclinical studies showed that ARC protects bone loss in an ovariectomy (OVX) mouse model. Conclusively, our data confirmed that ARC could potentially inhibit osteoclastogenesis by abrogating RANKL-induced MAPK, calcium, and NFATc1 signaling pathway, as well as by promoting the expression of ROS scavenging enzymes in Nrf2/Keap1/ARE signaling pathway, thereby 2 preventing OVX-induced bone loss. Thus, ARC may serve as a novel therapeutic agent for the treatment of osteoporosis.